2008
DOI: 10.1098/rspb.2008.1321
|View full text |Cite
|
Sign up to set email alerts
|

Disruptive selection in a bimodal population of Darwin's finches

Abstract: A key part of the ecological theory of adaptive radiation is disruptive selection during periods of sympatry. Some insight into this process might be gained by studying populations that are bimodal for dual-context traits, i.e. those showing adaptive divergence and also contributing to reproductive isolation. A population meeting these criteria is the medium ground finch (Geospiza fortis) of El Garrapatero, Santa Cruz Island, Galápagos. We examined patterns of selection in this population by relating individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
125
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(126 citation statements)
references
References 52 publications
1
125
0
Order By: Relevance
“…A few studies in other species reveal similar disruptive selection on other traits that influence non-random mating [8]. In Darwin's finches, for example, competition for food selects against intermediate beak size [44]; and beak size can affect song, which acts as a mating cue [45]. In sympatric stickleback morphs, traits that evolved in response to benthic and limnetic habitats are used as mating cues [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…A few studies in other species reveal similar disruptive selection on other traits that influence non-random mating [8]. In Darwin's finches, for example, competition for food selects against intermediate beak size [44]; and beak size can affect song, which acts as a mating cue [45]. In sympatric stickleback morphs, traits that evolved in response to benthic and limnetic habitats are used as mating cues [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…A review of avian heritabilities by Merilä and Sheldon (2001) showed large, significant heritability estimates for morphological traits ranging from 0.4 to 0.6 (40-60% of phenotypic variation due to genetic, rather than environmental, sources of variation). Directional, stabilizing, and disruptive selection on morphology have been documented in several avian species (Grant and Grant 1993, Brown and Brown 1998, Hendry et al 2009). In the Medium Ground-Finch (Geospiza fortis; Grant and Grant 1993), one of Darwin's finches in the Galápagos Islands, individuals with smaller bills had a higher chance of survival than those with larger bills after an El Niño, when smaller, soft seeds were the most common food.…”
Section: Introductionmentioning
confidence: 99%
“…As such, disruptive selection in an initial random mating population leads to evolutionary changes in mating patterns in all models and this, in consequence, contributes to reproductive isolation in subpopulations of the initial population [1], [10]. Competition for shared resources [11] [12] [13], adaptation to different resources [14] [15], and unequal distribution of resources throughout the environment [16] [17] are the underlying factors that could result in disruptive selective pressure. In addition to disruptive selection, other evolutionary factors play a leading role in sympatric speciation including sexual selection [18] [19], competition, and habitat preference [1].…”
Section: Introductionmentioning
confidence: 99%